A Survey of Studies on Adamantios Korais During the Nineteenth Century - Franghiscos, Emmanuel N. (The Historical Review/La Revue Historique, 2006)
With the exception of a biographical entry on Adamantios Korais (1748-1833) published in 1836 by the Hellenist G. R. L. de Sinner in Paris and of a university discourse by Professor Pericles Argyropoulos, published in 1850 in Athens, scholars and intellectuals in the newly founded kingdom of Greece had not included Korais among their research priorities. Eventually the academic foundations of research on Korais would be laid in the decade 1871-80. The Chiot merchants of Marseille in collaboration with a corresponding committee in Athens planned, among other manifestations honouring their compatriot Korais, the publication of his unpublished writings and his correspondence. The year 1881 saw the inauguration of the series Posthumously found writings with a volume edited by A. Mamoukas, who included a long biographical introduction. In 1885-6 Korais’ correspondence was published by Professor N. Damalas. Earlier, in 1877, in Paris from among the ranks of the "Association pour l’encouragement des études grecques en France", neohellenists Brunet de Presle and the Marquis de Queux de Saint-Hilaire had published Korais’ correspondence with the classicist Chardon de la Rochette during the French Revolution and with a number of other distinguished French philologists. In a separate edition they published his correspondence with the Swiss philosopher P. Prevost, and Queux de Saint-Hilaire translated and published in French in 1880 Korais’ correspondence with the Precentor of Smyrna D. Lotos during the Revolutionary period. In 1889-90 the Greek journalist in Trieste, D. Therianos, published a three-volume biography of Korais, which represents the most important milestone in Korais studies during the nineteenth century. Among more partial approaches to Korais’ life and work after Therianos, mention should be made of a critical study in 1903 by the diplomat scholar I. Gennadios, who called Damalas’ edition of Korais’ correspondence a shame for Greek letters. Although it was too early for nineteenth century authors to see Korais in the perspective of the European Enlightenment, they nevertheless have left important general synthetic works and prepared the ground for subsequent fuller editions of his correspondence.